Whole-Genome Sequencing Elucidates the Epidemiology of Multidrug-Resistant Acinetobacter baumannii in an Intensive Care Unit - Mao, Pu; Deng, Xiaolong; Yan, Leping; Wang, Ya; Jiang, Yueting; Zhang, Rong; Yang, Chun; Xu, Yonghao; Liu, Xiaoqing; Li, Yimin (Frontiers in Microbiology, 2021)
The nosocomial pathogen Acinetobacter baumannii is a frequent cause of hospital-acquired infections, particularly in critically ill patients, and is of serious concern due to its potential for acquired multidrug resistance. Whole-genome sequencing (WGS) is increasingly used to obtain a high-resolution view of relationships between isolates, which helps in controlling hospital-acquired infections. Here, we conducted a retrospective study to identify epidemic situations and assess the percentage of patient-to-patient transmission in intensive care units (ICUs). Multidrug-resistant A. baumannii (MDR-AB) were continuously isolated from the lower respiratory tract of different patients (at the first isolation in our ICU). We performed WGS, pulsed-field gel electrophoresis (PFGE), and multilocus-sequence typing (MLST) analyses to elucidate bacterial relatedness. From June 2017 to August 2018, A. baumannii complex strains were detected in 124 of 796 patients during their ICU stays, 103 of which were MDR-AB. We subjected 70 available MDR-AB strains to typing with WGS, PFGE, and MLST. Among the 70 A. baumannii isolates, 12 unique sequence types were identified with MLST. PFGE revealed 16 different closely related strains. Finally, WGS determined 23 patient-to-patient transmissions from 32 available acquisitions. Patient-to-patient transmission was the main mode of MDR-AB acquisition in our ICU. Our results demonstrated that WGS was a discriminatory technique for epidemiologic healthcare-infection studies. The technique should greatly benefit the identification of epidemic situations and controlling transmission events in the near future.